JOHANNES LEIMENA DALAM KESEHATAN IBU DAN ANAK DI INDONESIA (1946-1956) - Rella Astiannis (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
Mother and child welfare are very important in every country and one of the most important issues that should have an attention from the Minister of Health. Because it will affect a country’s progress and resilience. To increasing mother and child welfare, a comprehensive act such as economic, social, and health itself need to be implemented. For a newly independent state, that was a difficult thing to be done. Likewise, Indonesia after gained independence which also dealt with difficulties in improving their society health particularly mother and child health where at that time mortality were very high. Coupled with Indonesia which was confronted the revolutionary era (1945-1956) after gained its independence. Dr Johannes Leimena as a Minister of Health of the Republic of Indonesia from 1946 to 1956 was the one who has responsibility for public health in that period. This research was intended to analyse on increasing mother and child’s programs under Johannes Leimena era which referred to historical research methods such as heuristic, criticism, and historiography. Based on the result, in1940-1950 Indonesia has a low rate of population growth and one of them was due to the high rate of maternal and child mortality. At that time, Indonesia experienced an economic crisis that must strive to provide primary health care for mothers and children in Indonesia. So in 1951, Dr Johannes Leimena established BKIA (Balai Kesejahteraan Ibu dan Anak or Mother and Child Welfare Center) as a solution to these problems. BKIA is a regional health service centre including providing counselling to mothers and children. In its implementation in Indonesia, the BKIA assisted by UNICEF as an international child protection institution, as well as the government and the community who also participated in succeeded in the program. With its consistency, BKIA as the frontline for maternal and child health services that also served public health can reduce population's mortality rates in Indonesia and even gave an impact on increasing public awareness of the importance of maintaining health.